PERAN CAMAT DALAM PELAKSANAAN PEMBINAAN DAN PENGAWASAN PENYELENGGARAAN ADMINISTRASI PEMERINTAHAN DESA DI KECAMATAN PERAK KABUPATEN JOMBANG - Kismiati Ratri Ramadani; Muhammad Farid Ma'ruf (Publika, 2021)
The sub-district government is one of the organizers of regional autonomy. One of the duties of the District Government is to guide and supervise the implementation of village administration in accordance with the provisions of laws and regulations governing the village. The problems that exist in implementing the District Government are complex and dynamic. This is also triggered by the increasingly diverse needs of society in this modern era. In carrying out the task of fostering and supervising the implementation of village governance, of course the Camat and the ranks of the District Government experience obstacles in implementing it. The District Government also continues to strive to ensure that village governance runs well. The Perak Subdistrict Government itself has so far provided services to the village government as well as to the petitioners as much as possible. The role of the sub-district head as supervisor and supervisor of village administration is very important to spur village development. This is because the village still needs guidance from the Camat in the implementation of Village Government Administration. The purpose of this research is to find out, analyze, and explain the role of the sub-district head in the implementation of guidance and supervision of the implementation of Village Government Administration in Perak District, Jombang Regency. The research method used by researchers is a descriptive method with a qualitative approach. The results showed that the Head of the Perak Sub-District in carrying out guidance and supervision of Village Government Administration was accompanied by District Government staff, the Head of the Government Section and the Head of the Community and Village Empowerment Section also collaborated with village assistants from the Community and Village Empowerment Service to carry out technical guidance related to Administration. Village government is technically implemented by the Inspectorate of Jombang Regency. Coaching carried out by the Head of the Perak Sub-District in the form of a Conference with Village Officials, in particular the Village Head and the Village Secretary on a regular basis. In addition to conferences, the Camat in carrying out coaching also provides facilities with related agencies to increase the capacity of village officials. Supervision carried out by the Head of the Perak Sub-District is carried out directly and indirectly. Keywords: Role, Head of Sub-District, Guidance and Supervision, Village Government Administration Pemerintah kecamatan merupakan salah satu dari penyelenggara otonomi daerah. Salah satu tugas dari Pemerintah Kecamatan adalah membina dan mengawasi penyelenggaraan pemerintahan desa sesuai dengan ketentuan peraturan perundang-undangan yang mengatur desa. Permasalahan yang ada dalam pelaksanaan Pemerintah Kecamatan kompleks dan dinamis. Hal ini juga dipicu dengan adanya kebutuhan masyarakat pada era modern ini semakin beragam. Dalam menjalankan tugas membina dan mengawasi penyelenggaraan pemerintahan desa, tentunya Camat bersama jajaran Pemerintah Kecamatan mengalami kendala dalam melaksanakannya. Pemerintah Kecamatan juga terus berupaya untuk memastikan penyelenggaraan pemerintahan desa berjalan dengan baik. Pemerintah Kecamatan Perak sendiri sejauh ini melaksanakan pelayanan kepada pemerintahan desa juga warga pemohon dengan semaksimal mungkin. Peran Camat sebagai Pembina dan Pengawas Administrasi Pemerintahan Desa sangat penting untuk memacu perkembangan desa. Hal ini dikarenakan desa juga masih membutuhkan bimbingan dari Camat dalam pelaksanaan Administrasi Pemerintahan Desa. Tujuan dari penelitian ini adalah untuk mengetahui, menganalisis, dan menjelaskan peran Camat dalam pelaksanaan pembinaan dan pengawasan penyelenggaraan Administrasi Pemerintahan Desa di Kecamatan Perak Kabupaten Jombang. Metode penelitian yang digunakan oleh peneliti adalah metode deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa Camat Perak dalam melaksanakan pembinaan dan pengawasan Administrasi Pemerintahan Desa didampingi oleh staf Pemerintah Kecamatan Kepala Seksi Pemerintahan dan Kepala Seksi Pemberdayaan Masyarakat dan Desa juga berkerjasama dengan pendamping desa yang berasal dari Dinas Pemberdayaan Masyarakat dan Desa untuk melaksanakan pembinaan secara teknis Pengawasan terkait Administrasi Pemerintahan Desa dilaksanakan secara teknis oleh Inspektorat Kabupaten Jombang. Pembinaan yang dilaksanakan oleh Camat Perak dalam bentuk Konferensi dengan Perangkat Desa, khususnya Kepala Desa dengan Sekretaris Desa secara rutinan. Selain konferensi, Camat dalam melaksanakan pembinaan juga dengan memberikan fasilitas bersama dinas terkait untuk meningkatkan kapasitas aparatur desa. Pengawasan yang dilaksanakan oleh Camat Perak dilakukan secara langsung dan tidak langsung. Kata Kunci: Peran, Camat, Pembinaan dan Pengawasan, Administrasi Pemerintahan Desa